The Use of Questioning Strategy in Promoting Students Critical Thinking - Annisa Rizqa Rahima; Nurlaila Kadariyah; Nor Izzatil Hasanah (Universitas PGRI Yogyakarta, 2023)
Critical thinking is a crucial purpose that the education government wants to focus on to advance the production of quality education in Indonesia. The important role that cannot be separated from this progress is the teacher who is in charge of facilitating the students. Therefore, various strategies are used by teachers in facilitating students' critical thinking, one of which is by using a questioning strategy in class. In this study, descriptive qualitative based on theory was used in a book entitled Qualitative Data Analysis, A. Methods Sourcebook by Miles, et al. Furthermore, data analysis uses three stages, namely data condensation, data display and verification conclusion. The subjects of this study were four English teachers at the MTsN 2 Kota Banjarmasin. The techniques of data collection used observation and interviews. The results of this study show that the teachers used all of the types of questioning strategies proposed by Wu such as repetition, rephrasing, simplification, decomposition, and probing strategies in their lessons. And probing strategy was found which is the most chosen in promoting student critical thinking. Moreover, in its use in learning sessions it shows that the teacher actively uses the questioning strategy at the beginning, middle, also end of the lesson.